Combined transplantation of hiPSC-NSC and hMSC ameliorated neuroinflammation and promoted neuroregeneration in acute spinal cord injury - Xiaofeng Du; Desheng Kong; Ruiyun Guo; Boxin Liu; Jingjing He; Jinyu Zhang; Asiamah Ernest Amponsah; Huixian Cui; Jun Ma (Stem Cell Research & Therapy, 2024)
Abstract Background Spinal cord injury (SCI) is a serious clinical condition that has pathological changes such as increased neuroinflammation and nerve tissue damage, which eventually manifests as fibrosis of the injured segment and the development of a spinal cord cavity leading to loss of function. Cell-based therapy, such as mesenchymal stem cells (MSCs) and neural stem cells (NSCs) are promising treatment strategies for spinal cord injury via immunological regulation and neural replacement respectively. However, therapeutic efficacy is rare reported on combined transplantation of MSC and NSC in acute mice spinal cord injury even the potential reinforcement might be foreseen. Therefore, this study was conducted to investigate the safety and efficacy of co-transplanting of MSC and NSC sheets into an SCI mice model on the locomotor function and pathological changes of injured spinal cord. Methods To evaluate the therapeutic effects of combination cells, acute SCI mice model were established and combined transplantation of hiPSC-NSCs and hMSCs into the lesion site immediately after the injury. Basso mouse scale was used to perform the open-field tests of hind limb motor function at days post-operation (dpo) 1, 3, 5, and 7 after SCI and every week after surgery. Spinal cord and serum samples were collected at dpo 7, 14, and 28 to detect inflammatory and neurotrophic factors. Hematoxylin–eosin (H&E) staining, masson staining and transmission electron microscopy were used to evaluate the morphological changes, fibrosis area and ultrastructure of the spinal cord. Result M&N transplantation reduced fibrosis formation and the inflammation level while promoting the secretion of nerve growth factor and brain-derived neurotrophic factor. We observed significant reduction in damaged tissue and cavity area, with dramatic improvement in the M&N group. Compared with the Con group, the M&N group exhibited significantly improved behaviors, particularly limb coordination. Conclusion Combined transplantation of hiPSC-NSC and hMSC could significantly ameliorate neuroinflammation, promote neuroregeneration, and decrease spinal fibrosis degree in safe and effective pattern, which would be indicated as a novel potential cell treatment option. Graphical abstract